The witches enhanced with special sound effects - Dahl, Roald 1916-1990 (Penguin Audio, 2013)
Although his grandmother regularly tells him marvelous and terrible stories about witches, an English boy is scared stiff the day he runs into the Grand High Witch. When the witch transforms him into a mouse, the determined youngster decides to stop her from destroying the rest of England's children
Title from container
Compact discs
Duration: 4:30:00
Keywords: Witches / Juvenile fiction; England / Juvenile fiction; Witches / Fiction; England / Fiction; Fantasy; Witches; England; Audiobooks; Children's audiobooks; Fiction; Juvenile works; Fantasy fiction; Hörbuch; CD